Finding middle ground between intellectual arrogance and intellectual servility: Development and assessment of the limitations-owning intellectual humility scale. (1st April 2018) - Haggard, Megan; Rowatt, Wade C.; Leman, Joseph C.; Meagher, Benjamin; Moore, Courtney; Fergus, Thomas; Whitcomb, Dennis; Battaly, Heather; Baehr, Jason; Howard-Snyder, Dan
Abstract: Recent scholarship in intellectual humility (IH) has attempted to provide deeper understanding of the virtue as personality trait and its impact on an individual's thoughts, beliefs, and actions. A limitations-owning perspective of IH focuses on a proper recognition of the impact of intellectual limitations and a motivation to overcome them, placing it as the mean between intellectual arrogance and intellectual servility. We developed the Limitations-Owning Intellectual Humility Scale to assess this conception of IH with related personality constructs. In Studies 1 ( n  = 386) and 2 ( n  = 296), principal factor and confirmatory factor analyses revealed a three-factor model – owning one's intellectual limitations, appropriate discomfort with intellectual limitations, and love of learning. Study 3 ( n  = 322) demonstrated strong test-retest reliability of the measure over 5 months, while Study 4 ( n  = 612) revealed limitations-owning IH correlated negatively with dogmatism, closed-mindedness, and hubristic pride and positively with openness, assertiveness, authentic pride. It also predicted openness and closed-mindedness over and above education, social desirability, and other measures of IH. The limitations-owning understanding of IH and scale allow for a more nuanced, spectrum interpretation and measurement of the virtue, which directs future study inside and outside of psychology. Highlights: Intellectual humility (IH) is the mean between intellectual servility/arrogance. L-OIHS includes limitations-owning, lacking discomfort, and love of learning. L-OIHS predicts closed-mindedness and openness over other measures of IH.